Hyponatremia in Cirrhosis: Clinical Outcomes and Comparative Analysis of Different Treatment Approaches - Kranthi Dandi; Debabrata Banerjee; Amol S Dahale; Abhijeet S Karad; Yogesh S Bade (Journal of Clinical and Diagnostic Research)
Introduction: Hyponatremia is a common electrolyte disturbance in cirrhotic patients, resulting from impaired renal water excretion due to elevated levels of Antidiuretic Hormone (ADH) and is strongly associated with morbidity and mortality. Despite its significance, optimal management strategies remain debatable. Aim: To evaluate the impact of varying levels of hyponatremia on the clinical outcomes of patients with liver cirrhosis and assesses the efficacy of different treatment modalities. Materials and Methods: A prospective interventional study was conducted on 120 cirrhotic patients with hyponatremia at Dr. D.Y. Patil Medical College, Hospital and Research Centre, Pimpri, Pune, Maharashtra, India. Patients were categorised into five groups based on sodium levels: Group 1 (131-134 mEq/L), Group 2 (126-130 mEq/L), Group 3 (121-125 mEq/L), Group 4 (110-120 mEq/L), and Group 5 (<110 mEq/L). Treatment included albumin (20 g/day for the first three days, followed by 20 g/week), midodrine (5 mg three times daily), or a combination of both (albumin as above plus midodrine 5 mg three times daily). Patients were followed for six months, and sodium correction and mortality outcomes were analysed statistically. Results: Most patients presented with mild to moderate hyponatremia, with Groups 1 and 2 comprising 64.2% of the cohort. Sodium correction was most significant in Group 3 (121-125 mEq/L) with albumin plus midodrine (7.4-10.0 mEq/L at six months), while midodrine monotherapy showed the least improvement across all groups. Mortality was highest in Group 5 (<110 mEq/L; 100%) and among patients receiving midodrine alone in Group 4 (60%). Pairwise analysis in Group 2 revealed a significant advantage of combination therapy over midodrine alone (p-value=0.035). Conclusion: Hyponatremia significantly impacts survival. Combination therapy with albumin plus midodrine demonstrated superior sodium correction and trends toward better survival. Midodrine monotherapy was associated with the poorest outcomes.